Cytochrome P450 Metabolism of Betel Quid-Derived Compounds: Implications for the Development of Prevention Strategies for Oral and Pharyngeal Cancers. (1st August 2013) - Lin, Che-Yi; Pan, Tien-Szu; Ting, Chun-Chan; Liang, Shih-Shin; Huang, Shu-Hung; Liu, Hsiu-Yueh; Ko, Edward Cheng-Chuan; Wu, Chung-Wei; Tang, Jen-Yang; Chen, Ping-Ho
Abstract : Betel quid (BQ) products, with or without tobacco, have been classified by the International Agency for Research on Cancer (IARC) as group I human carcinogens that are associated with an elevated risk of oral potentially malignant disorders (OPMDs) and cancers of the oral cavity and pharynx. There are estimated 600 million BQ users worldwide. In Taiwan alone there are 2 million habitual users (approximately 10% of the population). Oral and pharyngeal cancers result from interactions between genes and environmental factors (BQ exposure). Cytochrome p450 ( CYP ) families are implicated in the metabolic activation of BQ- and areca nut-specific nitrosamines. In this review, we summarize the current knowledge base regarding CYP genetic variants and related oral disorders. In clinical applications, we focus on cancers of the oral cavity and pharynx and OPMDs associated with CYP gene polymorphisms, including CYP1A1, CYP2A6, CYP2E1, and CYP26B1 . Our discussion of CYP polymorphisms provides insight into the importance of screening tests in OPMDs patients for the prevention of oral and pharyngeal cancers. Future studies will establish a strong foundation for the development of chemoprevention strategies, polymorphism-based clinical diagnostic tools (e.g., specific single-nucleotide polymorphism (SNP) "barcodes"), and effective treatments for BQ-related oral disorders.